The Role of the “Political Elite” of the United States in Public Administration: Theoretical Foundations - Mirzabaev Kuatbay Baxitbaevich (International Journal of Advanced Science and Technology, 2020)
This article describes not only the administrative role of political elites in the USA but also the role of political elites as a subject of public administration and its role in making political strategic decisions and thus in determining the direction of public administration. Moreover, involvement equal participation of citizens in public administration, nowadays, is considered as the main factor and these aspects of public administration are taken into account in this research, such as Civic and political engagement and the new public management, which was carried out by USA Presidents at the end of twentieth and the beginning of the twenty-first century. Keywords: Elites, USA, Political elites, President, Public administration, New Public Management (NPM), Administrative reform.